CHILDHOOD EDUCATION: LUDIC ACTIVITIES THAT FAVOR THE TEACHING-LEARNING OF CHILDREN FROM 0 TO 02 YEARS OLD - Souza, Jacy Francisca Sampaio (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2022)
Studies have shown the importance of recreational activities in children's lives, because through games they learn and, in addition, provide full physical, cognitive, motor and social development. The purpose of this work is to present a brief study on the historical conceptions and their importance in the child's life involving the ludic. Thus, we present a theoretical approach on Early Childhood Education and its importance for the formation of children, especially those who participate in Early Childhood Education Institutions. Also point out the contributions of some renowned authors on the ludic (jokes and games) and how it is important for the child's cognitive and social development process, as well as contributing with some activities for children from 0 to 02 years old, being which can be adapted for older children. Based on these activity ideas, we can understand how relevant games and games are with a pedagogical objective, as it favors the teaching-learning process and makes the subject more critical and aware of his role in society. For this, a bibliographical research was carried out, with important subjects, based on a better understanding of this process.